Targeting chemoattractant chemokine (C–C motif) ligand 2 derived from astrocytes is a promising therapeutic approach in the treatment of neuromyelitis optica spectrum disorders - Wang, Yupeng; Bian, Jiangping; Yao, Mengyuan; Du, Li; Xu, Yun; Chang, Haoxiao; Cong, Hengri; Wei, Yuzhen; Xu, Wangshu; Wang, Huabing; Zhang, Xinghu; Geng, Xingchao; et al. (Frontiers in Immunology, 2023)
Introduction Aquaporin-4 immunoglobulin G (AQP4-IgG)-induced astrocytes injury is a key mechanism in the pathogenesis of neuromyelitis spectrum disorder (NMOSD), and although CCL2 is involved, its specific role has not been reported. We aimed to further investigate the role and potential mechanisms of CCL2 in AQP4-IgG-induced astrocyte injury. Methods First, we evaluated CCL2 levels in paired samples of subject patients by automated microfluidic platform, Ella®. Second, we knock down astrocyte's CCL2 gene in vitro and in vivo to define the function of CCL2 in AQP4-IgG-induced astrocyte injury. Third, astrocyte injury and brain injury in live mice were assessed by immunofluorescence staining and 7.0T MRI, respectively. Western blotting and high-content screening were conducted to clarify the activation of inflammatory signaling pathways, and changes in CCL2 mRNA and cytokine/chemokines were measured by qPCR technique and flow cytometry, respectively. Results There were greatly higher CSF-CCL2 levels in NMOSD patients than that in other non-inflammatory neurological diseases (OND) groups. Blocking astrocyte CCL2 gene expression can efficiently mitigate AQP4-IgG-induced damage in vitro and in vivo. Interestingly, prevention of CCL2 expression could decrease other inflammatory cytokines released, including IL-6 and IL-1β. Our data suggest that CCL2 involves in the initiation and plays a pivotal role in AQP4-IgG-damaged astrocytes. Discussion Our results indicate that CCL2 may serve as a promising candidate target for inflammatory disorder therapy, including NMOSD.